2014
DOI: 10.1021/ja501308s
|View full text |Cite
|
Sign up to set email alerts
|

Direct Visualization of Surface-Assisted Two-Dimensional Diyne Polycyclotrimerization

Abstract: Cyclotrimerization of alkynes to aromatics represents a promising approach to two-dimensional conjugated networks due to its single-reactant and atom-economy attributes, in comparison with other multicomponent coupling reactions. However, the reaction mechanism of alkyne cyclotrimerization has not yet been well understood due to characterization challenges. In this work, we take a surface reaction approach to study fundamental polymerization mechanism by using a diyne monomer named 4,4'-diethynyl-1,1'-biphenyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
142
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 128 publications
(147 citation statements)
references
References 26 publications
4
142
0
1
Order By: Relevance
“…Zhou et al suggests that the reactionp roducts of the alkyne cyclotrimerization show at hree-fold symmetry or at hree-fork shape, with dihedron angles of 608,1 208,a nd 1808. [14] Liu et al also observed similar results for alkyne cyclotrimerization on ag old surface, and they found that three 1,3,5-tris(4-ethynylphenyl)benzene molecules are covalently bonded to each other through ac ommon benzene ring formed from the three alkyne groups. [11] Based on the similarities of the molecular structure, the large cloverlike features are proposed to be the cyclotrimerized ETPAt rimers.…”
Section: Resultsmentioning
confidence: 64%
See 1 more Smart Citation
“…Zhou et al suggests that the reactionp roducts of the alkyne cyclotrimerization show at hree-fold symmetry or at hree-fork shape, with dihedron angles of 608,1 208,a nd 1808. [14] Liu et al also observed similar results for alkyne cyclotrimerization on ag old surface, and they found that three 1,3,5-tris(4-ethynylphenyl)benzene molecules are covalently bonded to each other through ac ommon benzene ring formed from the three alkyne groups. [11] Based on the similarities of the molecular structure, the large cloverlike features are proposed to be the cyclotrimerized ETPAt rimers.…”
Section: Resultsmentioning
confidence: 64%
“…[13] The occurrence of at wo-step [2+ +2+ +2] cyclization reactiono nt he Au(111)s urface suggestst hat the gold surface contributes to the formation of ab enzene moietyt hrough three acetylene units. [14] Direct observations of the internal bond structures of the reactant alkynes and their products on Ag(100) and Au(111)f urtherr eveal that much more complex surface reactionm echanismsa re present underlying thermally induced alkyne-based cyclization. [15] Although much effort has been made to investigate reaction mechanisms of alkyne-based reactions, the exploration of supramolecular structures ynthesis through alkyne-basedr eactions is limited.…”
Section: Introductionmentioning
confidence: 99%
“…Cyclotrimerization of 9 on Au(111) at 373 K gave rise to structures with branched and hexagonal motifs with two types of molecular interconnections, I1 and I2 (Figure 7b). 39 The more uniform polyphenylene structure in Figure 7c (molecular …”
Section: Strategiesmentioning
confidence: 99%
“…24,25 Very recently, a new protocol, for synthesizing 2D porous networks, was proposed by aryl alkyne cyclotrimerizations on metal surfaces. 26,27 Cyclotrimerization reactions are seldom reported to construct 2D materials on surfaces under ultra high vacuum (UHV), although they have been extensively utilized in the building of covalent organic frameworks (COF) materials in solutions. 28,29 Scheme 1.…”
mentioning
confidence: 99%